Using social networking sites to share information in Education (Al-Mansour Journal, 2022)
Provide information and communication technologies every day new services , including services ( Web 2.0) , which are through social networking sites , which have become valuable and of great significance for the communities , including the student community and the aim of this study to identify the purpose of the use of social networking sites and their impact on an individual's life , especially young people and the use of the case study method and the way the distribution of the questionnaire to students of the Faculty of Al-Mansour University for the academic year (2012-2013) , and was a representative sample of (100 ) students and of the results of the study and the proportion (37%) are using sites for educational purposes and with a desire to communicate in order to support the curriculum academic and easy and economical these services in communication , with a high proportion of the use of the social networking site ( Facebook ) Among the recommendations the need for colleges and scientific departments and information centers and libraries to find sites social networking with bind staff teaching in communion with the students in presenting scientific material and receiving duties and put lectures on sites for the purpose of discussion for more than once.
Keywords: Social networking sites; Facebook; Advantages and disadvantages for social networking; Mansour University college